Kepraktisan Game Edukasi Berbasis Wordwall pada Pelajaran IPAS Bab 1 Kelas IV SDN 41 Pontianak Utara - Andini, Della Putri; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (AS-SABIQUN, 2024)
The research carried out intends to develop educational games in learning activities based on wordwall games created for grade IV science and science lessons at SDN 41 North Pontianak which fulfill the requirements to assist with learning evaluation activities in the Merdeka curriculum. This research method is an RnD method with the model namely ADDIE. This research data was obtained by involving 1 class with 25 class IV students at State Elementary School 41 North Pontianak, 1 media and material expert validator and 1 media and material expert validator again. The techniques for collecting data in this research are observation, interviews and questionnaires. The results after the research show that the process of developing wordwall-based educational games in science lessons in class IV elementary schools has gone through 4 stages of the ADDIE model research from the 5 stages. Wordwall game development product validity activities produced very valid criteria with an average score of 82.81% for the material aspect and 91.91% with very valid criteria for the media aspect. After carrying out practicality, the results obtained were that the wordwall-based educational game developed had a practicality level of 93.7% in the "very practical" category so that the media was declared very suitable and practical for use in the classroom learning process.